Analisis Hukum Islam terhadap Status Harta Koin Shopee - Darmawati, Darmawati; Fathoni, Khoirul (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Shopee coins are virtual currencies issued by shopee, this virtual money can be obtained when someone makes a shopping transaction at shopee, 1 shopee coin is valued at 1 rupiah. The use of shopee coins for shopping discounts on the shopee marketplace is limited, that is, from the balance of shopee coins owned by the user, only 25% of the total buyer purchases can be exchanged, for example, a user wants to spend 100 thousand rupiah, the shopee coins that can be used to shop are only 25 thousand rupiah or 25 thousand shopee coins. Shopee coins also have an expiration date, if they are not used for three months, the coins will be forfeited. This thesis reports the results of the research, with the formulation of the problem (1) how is the process of ownership of shopee coins? (2) what is the status of shopee coin assets in the perspective of Islamic law? (3) how is the maslahah value in the practice of using shopee coins in buying and selling transactions at shopee?. This study uses a qualitative method in the location of the district of Ponorogo, with data collection procedures through interview techniques, documentation, and data analysis. The data collected is related to checking the validity of the data by comparing the results of various sources, namely books, documents related to this research, observations, interviews, and documentation. Based on the results of data analysis, it is concluded that 1) The process of ownership of shopee coin assets is carried out by creating a shopee account, through shopping giving reviews and even through games provided by shopee, shopee coins will automatically enter the user's account. 2) The status of the property of shopee coins is concluded as beneficial assets that are mauzhuf fi al-dzimmah or debt assets guaranteed by the shopee marketplace. 3) The value of maslahah in the application of shopee coins is the value of the guarantor's assets in the relationship in al-dain (debt guarantee), in al-ain (physical security), and dlaman an-nafsi (life insurance)